2022
DOI: 10.3389/fmolb.2022.942406
|View full text |Cite
|
Sign up to set email alerts
|

Truncated lubricin glycans in osteoarthritis stimulate the synoviocyte secretion of VEGFA, IL-8, and MIP-1α: Interplay between O-linked glycosylation and inflammatory cytokines

Abstract: The primary aim of the study was to identify inflammatory markers relevant for osteoarthritis (OA)-related systemic (plasma) and local (synovial fluid, SF) inflammation. From this, we looked for inflammatory markers that coincided with the increased amount of O-linked Tn antigen (GalNAcα1-Ser/Thr) glycan on SF lubricin. Inflammatory markers in plasma and SF in OA patients and controls were measured using a 44-multiplex immunoassay. We found consistently 29 markers detected in both plasma and SF. The difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…7j) demonstrated that adding tryptase β alone to human synovial fluid is sufficient to induce a change a gene expression in NF-κB1 and RELA. In addition, we previously demonstrated that altered truncated PRG4 glycans can stimulate the synoviocyte secretion of vascular endothelial growth factor a (VEGFA), IL8 and CCL3 65 . Recombinant PRG4 can induce NF-κB activation and requires tryptase β activity.…”
Section: Discussionmentioning
confidence: 99%
“…7j) demonstrated that adding tryptase β alone to human synovial fluid is sufficient to induce a change a gene expression in NF-κB1 and RELA. In addition, we previously demonstrated that altered truncated PRG4 glycans can stimulate the synoviocyte secretion of vascular endothelial growth factor a (VEGFA), IL8 and CCL3 65 . Recombinant PRG4 can induce NF-κB activation and requires tryptase β activity.…”
Section: Discussionmentioning
confidence: 99%
“…The change of plasma glycosylation in OA with decreased amount of SNA epitopes is quite different compared to OA regarding SF lubricin where the glycans are shown to be more truncated and expected to have more Tn antigens compared to controls 10 . The origin of this lubricin SNA depleted glycoform found in the OA-cohort ‘s plasma is unknown and whether it is caused by alterations in catabolic and/or anabolic processes.…”
Section: Discussionmentioning
confidence: 86%
“…In OA, there is an increase of truncated structures such as Tn-antigen (GalNAcα1-Ser/Thr) in SF lubricin 10 . Lubricin with truncated glycosylation acts as a signaling molecule that stimulates synoviocytes influencing the level of inflammatory cytokines, chemokines, and growth factors 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations